To solve the quadratic equation \( 2x^2 - 5x - 6 = 0 \), we can use the quadratic formula:
\[ x = \frac{{-b \pm \sqrt{{b^2 - 4ac}}}}{2a} \]
In this equation:
- \( a = 2 \)
- \( b = -5 \)
- \( c = -6 \)
Now, plug these values into the formula.
- Calculate the discriminant \( b^2 - 4ac \):
\[ (-5)^2 - 4 \cdot 2 \cdot (-6) = 25 + 48 = 73 \]
- Now substitute back into the quadratic formula:
\[ x = \frac{{5 \pm \sqrt{73}}}{4} \]
-
Calculate \( \sqrt{73} \) which is approximately \( 8.54 \).
-
Now calculate the two potential solutions:
\[ x_1 = \frac{{5 + 8.54}}{4} \approx \frac{{13.54}}{4} \approx 3.385 \]
\[ x_2 = \frac{{5 - 8.54}}{4} \approx \frac{{-3.54}}{4} \approx -0.885 \]
Rounding \(-0.885\) to the nearest hundredth gives \(-0.89\).
Thus, the solution to the quadratic equation \( 2x^2 - 5x - 6 = 0 \) that matches one of the provided options is:
x = -0.89.